Conflict of Interest Disclosure Among the Highest Earning Physicians Receiving Compensation From Vascular Device Companies. Issue 10 (October 2022) - Al-Khouja, Fares; Nyam, Amanda; Sheehan, Brian; Sullivan, Brittany; Kabutey, Nii-Kabu; Stamos, Michael J.; Pigazzi, Alessio; Jafari, Mehraneh D.
Objective: To characterize the association between payments made by vascular device companies to clinicians, and the conflict of interest (COI) declarations on relevant publications. Summary Background Data: Close association between medical device companies and clinicians is essential in the advancement of surgical technology. When evaluating the efficacy of novel equipment, identification of these relationships can minimize the risk of bias in relevant studies. Methods: Using the Open Payments Database (OPD), the 10 highest compensated clinicians from 10 vascular device companies were identified. In the population based bibliometric analysis, general payments, number of payments, h-index, and academic rank were identified. PubMed and Scopus were queried to identify author publications. Relevance to payment received and COI disclosures were identified for each article. Results: The physicians identified earned $33, 442, 266.74 with a median of $92, 500 in 2017. The authors published an average of 6.46+/−9.08 articles in 2018. Relevant COI was identified in 74%. In 50.5% of the relevant publications was a COI declared. The median h index of authors was 18+/−23. Community based physicians had a higher rate of COI disclosure (65.6%) compared to academic physicians (47.6%) (P = .008). Low h-index authors had a higher rate of COI declaration (71.4%) compared to high h-index (43.6%) (P = .001). Conclusion: A high degree of inconsistency was found between self-declared COI and relevant articles published by the highest compensated physicians. We propose a policy of full disclosure and the addition of a link to each author's OPD page on all publications to increase access to potential COI.